Protein inhibitors of angiogenesis in cancer therapy - Olbryt, Magdalena; Szala, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2005)
Antiangiogenic therapy is one of the most intensively studied approaches to cancer treatment. The goal of this strategy is to inhibit growth of primary tomors and metastases through blocking new blood vessels’ formation in tumor mass. The antiangiogenic drug is an angiogenesis inhibitor that interferes with endothelial cell proliferation, endothelial cell migration or blood vessel tube formation. Most antiangiogenic factors exhibit cytostatic mode of action, are well tolerated and do not induce resistance. One group of anti-angiogenic agents consists of proteolytic fragments of endogenous proteins of which the best known are angiostatin and endostatin. All antiangiogenic polypeptides strongly inhibited angiogenesis and growth of different tumor cell lines in preclinical studies. An increased efficacy of these agents was observed when combined with radiotherapy or chemotherapy as well as when two different polypeptides were delivered together. Some angiogenesis inhibitors are currently subjected to clinical trials. Such studies have revealed some obstacles with regard to evaluating the therapeutic potential of these drugs. It was difficult to assess their antiangiogenic activity in vivo (lack of reliable biologic end points, difficulty in determining of maximally tolerated dose), to evaluate antitumoural efficacy or setting appropriate scheduling of drugs. Inspite of high efficacy in inhibiting experimental tumours, most anti- -angiogenic agents did not show similar activity in clinical trials. Presumably, this discrepancy stems mainly from imperfection of animal models and the specificity of clinical studies in which drugs are tested on heterogenous groups of patients with advanced disease. In view of the gathered results it seems that the anti-angiogenic agents may be used mostly to prevent progression of early-stage cancer and as adjuvant therapy combined with cytotoxic strategies. In this paper, we present therapeutic results of most antiangiogenic polypeptides used in preclinical studies and discuss obstacles and perspectives of antiangiogenic therapy.